Vaginal hysterectomy for pelvic organ prolapse in Nepal - Sah, DK; Doshi, NR; Das, CR (Kathmandu University Medical Journal, 2010)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Background: UVP is a significant Public Health Problem in Nepal. This problem is mainly prevalent in rural areas where the women are socio - economically less privileged and cannot afford the costs of treatment. Objective: An analysis of peri operative and post operative complications of vaginal hysterectomies for pelvic organ prolapse. Materials and methods: A hospital based prospective study was carried out in the department of obstetrics and gynaecology, NGMC followed up from the time of operation to time of discharge. Results: 632 cases underwent vaginal hysterectomy with financial support from UNFPA. There were no operative complications. The most common post operative complications as noted were retention of urine, pelvic infection & pelvic abscess. In two cases laparotomy was done for haemoperitoneum. Pelvic abscess was drained vaginally. Mortality was nil. Conclusion: Proper screening before operation is the key to reduce operative as well as peri operative complications. Key words: vaginal hysterectomy; pelvic organ prolapse; peri operative complications of vaginal hysterectomy DOI: 10.3126/kumj.v8i2.3576 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 281-284